Advance of Amphiphilic Block Copolymeric Micelles as Drug Delivery: A Review - Jiao, Zhen; Wang, Xing; Chen, Zhiming (Asian Journal of Chemistry, 2012)
The poor water-solubility of the anticancer drugs cause significant problems during clinical application. The amphiphilic block copolymeric micelles are the most promising system to solve this problem. This manuscript introduce the formation of these polymers as well as the preparation of the polymers and the micelles. The newly developments which include the micelles prepared methods based on supercritical carbon dioxide (ScCO2) and the tumor targeting drug-loaded micelles are also discussed in this paper.